Selective laser melting of Al-Cu-Fe based alloys using elemental powder blends - Shtablavyi, Ihor; Kulyk, Yuri; Pauk, Andrii; Popilovskyi, Nazar; Yatsevych, Maryna; Mudry, Stepan (Physics and Chemistry of Solid State, 2026)
In this work, the conditions for obtaining the Al63Cu25Fe12 alloy from a mixture of elemental powders by selective laser melting were investigated. In addition to directly synthesizing the alloy using the mentioned method, the aim of this work was also to identify the conditions for the formation of quasi-crystalline phases, which have special mechanical properties. Selective laser melting was performed at different powers and geometries of laser irradiation in air and in vacuum. Scanning electron microscopy and X-ray phase analysis methods were used to study the prepared alloys. It has been shown that, in addition to the generally accepted modes of laser alloy synthesis, focusing the laser beam on the surface of the samples plays an important role in this process.